Liver function test abnormalities at hospital admission are associated with severe course of SARS-CoV-2 infection: a prospective cohort study. Issue 10 (29th January 2021) - Weber, Sabine; Hellmuth, Johannes C; Scherer, Clemens; Muenchhoff, Maximilian; Mayerle, Julia; Gerbes, Alexander L
Abstract : Objective: Liver injury has frequently been reported in COVID-19 patients. The clinical relevance of liver injury related to SARS-CoV-2 infection remains unclear with a need for prospective studies on the impact of liver function test (LFT) abnormalities at baseline. Design: Data of 217 patients without pre-existing liver disease prospectively included in the COVID-19 registry of the LMU university hospital were analysed in order to assess the association of abnormal LFT at admission and course of the disease. Severe course was defined as admission to the intensive care unit (ICU) or as COVID-19-related death. Results: Abnormal LFT at baseline was present in 58% of patients, with a predominant elevation of aspartate aminotransferase (AST) (42%), gamma-glutamyltransferase (GGT) (37%) and alanine aminotransferase (ALT) (27%), hypoalbuminaemia was observed in 33%. Elevation of ALT and GGT, as well as hypoalbuminaemia, was associated with higher proportions of patients requiring ICU treatment and mechanical ventilation. After adjusting for age, gender and comorbidities, hypoalbuminaemia combined with abnormal AST or GGT at hospital admission was a highly significant independent risk factor for ICU admission (OR 46.22 and 38.8, respectively) and for a composite endpoint of ICU admission and/or COVID-19-related death (OR 42.0 and 26.9, respectively). Conclusion: Abnormal LFTs at hospital admission, in particular GGT and albumin, are associated with a severe course of SARS-CoV-2 infection.